Kajian Unjuk Kerja Metode Hidrograf Satuan Sintetik Untuk Penetapan Banjir Rancangan Pada Das Di Pulau Jawa (Studi Kasus Das Cimanuk Hulu) - Gunawan, Amaltia (Dinamika Rekayasa, 2007)
Recently, new methods for calculating unit hydrograph are growing fast. Therefore, an idea to compare each methods is necessary needed to ensure which method fits the most to the caracteristic of a particular basin. These some Synthetic Unit Hydrograph (SUH) methods which are Nakayasu SUH, Snyder SUH (in HEC-HMS), and GAMA I SUH, compared with Unit Hydrograph calculation method Collins, which is based its formula on measured hydrograph data. By doing summary to the results, one conclusion is received that the hydrograph by Snyder SUH in HEC-HMS fits the most to the hydrograph by Collins. Results of this study is aimed to ensure the researchers that Snyder SUH in HEC-HMS can also be alternative to make some hydrograph analysis